E-cigarette use is prospectively associated with initiation of cannabis among college students. (July 2020) - Ksinan, Albert J.; Spindle, Tory R.; Thomas, Nathaniel S.; Eissenberg, Thomas; Dick, Danielle M.; ,
Highlights: Tested longitudinal association of e-cigarette and cannabis use. Large, diverse college sample (N = 4, 670) assessed over four years. Bidirectional effects for e-cigarette and cannabis use were found. E-cigarettes showed effects on later cannabis use even among cigarette nonsmokers. Abstract: E-cigarettes have dramatically increased in popularity among youth. Coincident with expanded legalization, young adults' use of cannabis (marijuana) has also steadily increased in recent years. Use of tobacco products can increase the chances of later cannabis initiation among youth. However, most longitudinal investigations of tobacco and cannabis use patterns have focused on tobacco cigarettes, included adolescents as opposed to young adults, and have only employed two timepoints. The current study examined prospective associations between e-cigarette and cannabis use in a large, diverse college sample assessed over four timepoints (freshman – senior year; N = 4, 670). E-cigarette use and cannabis use were modelled in a four-wave cross-lagged model. The results showed significant bidirectional associations between both substances, even after controlling for time-varying levels of depressive symptoms, alcohol use, and polysubstance use, sensation seeking, demographic variables, concurrent associations and previous levels of use. Moreover, the significance of the predictive path from e-cigarette use to later cannabis use remained unchanged when we ran the same model, but restricted the sample to e-cigarette-only users (i.e., never cigarette smokers), whereas only one prospective path from cannabis to e-cigarette use was significant in this subsample. The current findings suggest that the association of e-cigarette use and cannabis use is likely bidirectional, with stronger support for the link from e-cigarette use to later cannabis use, above and beyond cigarette use. As e-cigarettes gain further hold of the tobacco product market share and cannabis legalization continues to expand, data such as these will be critical for informing regulatory decisions for e-cigarettes and cannabis, particularly involving their accessibility to youth and young adults.